Analysis of the Role of Dynamic Filing Systems in Supporting Operational Management - Rahmadana, Ogi; Atika; Dharma, Budi (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2024)
Archives have an important role in providing information for an institution or agency in making decisions and formulating policies. This research aims to analyze the role of a dynamic archiving system in supporting operational management at PT Pelindo Multi Terminal. The research method used is qualitative with a case study approach. Data was obtained through in-depth interviews, observation and analysis of documents related to archive management in the company. The research results show that dynamic archiving systems play an important role in providing a good source of information for company leaders. Organizing archives using appropriate tools and equipment, managing appropriate types of archives, as well as planned methods for depreciation and destruction of archives, are important factors in maintaining the smoothness and success of the archives system. Support from competent human resources is also a crucial aspect in maintaining the effectiveness of archive management. Thus, this research contributes to the understanding of the importance of a dynamic archiving system in supporting operational management at PT Pelindo Multi Terminal. The novelty of this research is that it focuses on how dynamic archiving systems have a direct impact on operational management, including efficiency analysis in the documentation process, reducing document search time, and the impact on strategic decision making. This research will also add value by providing a case study of implementing a dynamic archiving system specifically for the port industry. It provides specific insights into the challenges and benefits port companies face in implementing these systems.